Sport, Spirituality, and Brand Experience: Examining Marathon Participant Loyalty in the Contemporary Islamic Lifestyle Ecosystem - Yudiarto Perdana Putra; Sudarmiatin; Budi Eko Soetjipto; Cipto Wardoyo; Afif Nur Rahmadi (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
This study examines the interconnections among sport, spirituality, and brand experience in shaping marathon participants' loyalty within the contemporary Islamic lifestyle ecosystem. The increasing emergence of Islamic-themed marathons—incorporating elements of da’wah, charity, and halal-oriented community engagement—indicates that sporting events are no longer perceived solely as arenas of physical competition. Instead, they function as spaces for meaning-making, spiritual connection, and the expression of modern religious identity. Using a phenomenological qualitative approach, this study explores how participants interpret and narrate their experiences in Islamic-themed marathon events. Particular attention is given to how the event’s religious atmosphere, embedded spiritual values, and participants’ interactions with the organisers’ symbols, narratives, and identities cultivate emotional attachment. Data were collected through in-depth interviews, field observations, and analysis of digital documents related to various Islamic running events, allowing for a comprehensive understanding of lived experiences and symbolic engagement. The findings reveal that both personal and communal dimensions of spirituality play a crucial role in reinforcing emotional bonds between participants and event organisers. These bonds extend beyond satisfaction with event quality, shaping a more profound sense of belonging, shared purpose, and value alignment. As a result, participants demonstrate stronger intentions to re-participate and to recommend the events within their social networks. This study contributes to Islamic marketing and consumer culture scholarship by highlighting how contemporary sports practices can be strategically integrated with spiritual values. It shows that within the expanding Islamic lifestyle industry, brand loyalty can be cultivated not only through functional or experiential benefits but also through spiritually meaningful engagement.